Rare bird documentation form for Northern Goshawk at Sweet Marsh, 1983 - Myers, Robert K.et al (1983)
Rare bird documentation form for a Northern Goshawk at Sweet Marsh in Bremer County, IA on November 11, 1983. Epson - sheet feed